Analysis of Ovarian Cancer Risk Factor : A Systematic Review - Ida Nurhidayah; Restuning Widiasih; Ermiati Ermiati (Universitas Pendidikan Indonesia, 2022)
AbstractOvarian cancer risk factors are health problems that pose a risk to women's survival. Health workers and women must recognize the risk factors that can lead to ovarian cancer as early prevention. The objective of this systematic review is to analyze various risk factors for ovarian cancer. The systematic review method uses 4 databases, namely Proquest, Pubmed, Willey, and Ebsco, with the keywords ovarian cancer AND risk factors AND determinant factors OR predisposition factors AND incident OR prevalence. Inclusion criteria include relevant articles according to the topic, type of quantitative research, no year limit specified, and search using English. The initial number of searches obtained was 3,507 articles, the selection results used the PRISMA flow and used JBI tools so that 15 articles were reviewed. The results of the study identified risk factors for ovarian cancer, namely reproductive factors, lifestyle, family history, history of benign ovarian tumors, endometriosis, and endometriomas. Reproductive factors are the factors most associated with the occurrence of ovarian cancer. AbstrakFaktor risiko kanker ovarium merupakan masalah kesehatan yang berisiko terhadap kelangsungan hidup perempuan. Petugas kesehatan dan perempuan harus mengenal faktor risiko yang dapat menyebabkan terjadinya kanker ovarium sebagai pencegahan secara dini. Tujuan sistematik review untuk menganalisis berbagai faktor risiko kanker ovarium. Metode systematic review menggunakan 4 database, yaitu Proquest, Pubmed, Willey dan Ebsco, dengan kata kunci ovarian cancer AND risk factors AND determinant factors OR predisposition factors AND incident OR prevalence. Kriteria inklusi meliputi artikel relevan sesuai dengan topik, jenis penelitian kuantitatif, tidak ditentukan batas tahun, pencarian menggunakan Bahasa Inggris. Jumlah awal pencarian didapat 3.507 artikel, hasil seleksi menggunakan alur PRISMA dan menggunakan tools JBI sehingga terdapat final artikel akan di review sebanyak 15 artikel. Hasil penelitian mengidentifikasi faktor risiko kanker ovarium, yakni faktor reproduksi, gaya hidup, riwayat keluarga, riwayat penyakit tumor ovarium jinak, endometriosis dan endometrioma. Faktor reproduksi merupakan faktor yang paling banyak berhubungan dengan terjadinya kanker ovarium.